HVSR-Based Microzonation of Natural Frequency, Amplification, Vulnerability Index, and Ground Shear-Strain in Malang City, East Java - Situmeang, Adedio Daniel; Saputra, M. Rizky; Ramadhan, Yuansyah Dhaniar; Cholisatin, Safira Nur; Asyfiya, Divana Zumrotul; Madlazim, Madlazim; Fahmi, Muhammad Nurul; Safrian, Alif Haidar; Putri, Rasamala I.W; Realita, Arie (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2026)
Seismic activity in Malang City is very high due to tectonic dynamics in the subduction zone between the Indian-Australian and Eurasian plates and the active local faultsm, including the northeast-southwest trending Watukosek Fault, and the east-west fault around the Pasuruan Fault, which have the potential to cause damaging ground shaking in Malang City. The BMKG also recorded an earthquake with a magnitude of 4.5 Mw on March 16, 2025. Based on these events, this study was conducted to analyze the vulnerability of Malang City, East Java, using the Horizontal-Vertical Spectral Ratio (HVSR) method by integrating the parameters of natural frequency (f0), amplification (Ag), soil vulnerability index (Kg), and Ground Shear-Strain (γ). A total of 19 points were processed using Geopsy software to obtain the HVSR curve and obtain the f₀ and Ag values, while Kg and γ were obtained from processing the HVSR parameters and then mapped through spatial interpolation in ArcGIS. The results of data processing and analysis show that several points in Malang City have f0 1.448 - 9.938 Hz with amplification 1.704 - 6.639 and soil vulnerability index values 0.383 - 14.871, as well as shear strain values up to 0.009. Zones are mainly concentrated by high amplification and vulnerability are mainly concentrated in the northern part of Kedungkandang District, the eastern part of Blimbing District, and parts of Lowokwaru District, which are dominated by higher frequencies with low amplification, as well as the western part of Sukun District, indicating a high level of earthquake risk. While previous studies primarily utilized only utilized natural frequencies and amplification, whereas this study offers HVSR-based microzonation by integrating dynamic soil parameters (f₀, Ag, Kg, and γ).